METHODS FOR THE CHOOSING THE RATIONAL COMBINATION AND COMPARISON OF THE CHARACTERISTICS AND FACTORS OF THE EFFICIENCY OF THE PRODUCTION PROCESSES AND TECHNOLOGIES OF THE BOREHOLE DRILLING - V. V. Kulikov (Известия высших учебных заведений: Геология и разведка)
The paper considers the methods for choosing the rational combination and comparison of the measured characteristic sand factors, used during decisions making, designing and assessment the efficiency of the production processes and boreholes drilling technologies. When choosing the rational comparison of the homogeneous characteristic sand factors, in abas is of the formalized representation of the methods the reisa coordinate geometrical approach, based on the definition of the maximum (minimum) distance between the points, located in the arithmetical n-dimensional Euclidean space and characterized by the given object of the analysis and decision making. Formalized representation of the methods for the choosing the rational combination of non-homogeneous as well as the homogeneous characteristics and factors bases on the definition of the maximum (minimum) value of the product of the their values. The examples are given from the different fields of the drilling production processes and technologies.